Establishing biomarkers and clinical endpoints in myotonic dystrophy type 1 (END-DM1): Protocol of an international natural history study - Karlien Mul; Kate Eichinger; Man Hung; Valeria A. Sansone; Cynthia Gagnon; Sub Subramony; Richard H. Roxburgh; Johanna Hamel; Jeffrey M. Statland; Bakri Elsheikh; Chris Turner; Jacinda Sampson; et al. (PLoS ONE, 2025)
Background Myotonic dystrophy type 1 (DM1) is an autosomal dominant inherited multi-system disorder that affects skeletal muscles but also many other organ systems. Molecular targets have been identified and targeted therapies are being developed and tested in first-in-human clinical trials. However, insufficient knowledge of the phenotypic heterogeneity and natural course of the disease, together with a lack of reliable biomarkers, complicate the design of clinical trials. Methods The main objectives of this study are to 1) characterize the phenotypic heterogeneity and disease progression of DM1 in a large cohort; 2) identify baseline characteristics that predict subsequent progression; 3) validate RNA biomarkers of disease severity. This is a prospective, multi-site observational study with a follow-up period of 24 months including approximately 700 adult DM1 patients. Visits will occur at baseline, and months 12 and 24. All patients will undergo strength testing, myotonia assessment, a battery of functional outcome assessments, spirometry, and complete various questionnaires and cognitive tests. Blood and urine samples will be taken at each visit for biomarker studies. A subset of 60 patients will undergo a muscle biopsy at baseline and at an additional 3-month visit. The sensitivity to disease progression and minimally clinically important differences will be determined for the various clinical outcome measures. Associations between baseline patient characteristics and the rate of disease progression will be evaluated. Discussion The results of this large international study on DM1 will contribute to optimizing clinical trial design. Both data and biological samples will be collected for future research as well. Trial registration Clinicaltrials.gov NCT03981575